Respuestas
Respuesta dada por:
1
despejo y en la ec 1
![y= \frac{6+2x}{4} y= \frac{6+2x}{4}](https://tex.z-dn.net/?f=y%3D+%5Cfrac%7B6%2B2x%7D%7B4%7D+)
reemplazo y en ec 2 x+y=3
![x+ \frac{6+2x}{4}=3 x+ \frac{6+2x}{4}=3](https://tex.z-dn.net/?f=x%2B+%5Cfrac%7B6%2B2x%7D%7B4%7D%3D3+)
![\frac{4x}{4}+ \frac{2x}{4}=3- \frac{6}{4} \frac{4x}{4}+ \frac{2x}{4}=3- \frac{6}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B4x%7D%7B4%7D%2B+%5Cfrac%7B2x%7D%7B4%7D%3D3-+%5Cfrac%7B6%7D%7B4%7D+++)
![\frac{6x}{4}= \frac{6}{4} simplificando \frac{6x}{4}= \frac{6}{4} simplificando](https://tex.z-dn.net/?f=+%5Cfrac%7B6x%7D%7B4%7D%3D+%5Cfrac%7B6%7D%7B4%7D++simplificando)
x=1
y=(6+2x)/4 =8/4=2
x=1 y=2
reemplazo y en ec 2 x+y=3
x=1
y=(6+2x)/4 =8/4=2
x=1 y=2
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años